Types, forms and dynamics of deviant behavior of teenagers - Баялиева, Гүлзира; Жундибаева, Турархан (Pedagogy and Psychology, 2020)
The article discusses the types, forms and dynamics of deviant behavior, which are currently common among adolescents. The term “deviant” is also grouped into a number of leading theoretical fields, biological, psychological and social sciences, in which the conceptual approaches of foreign researchers to variations dominate in the fields of research. The areas and levels of abnormalities found in adolescents are described. Studying the deviant behavior of adolescents requires its separation from other population groups and the determination of specific social indicators of deviation. When determining the characteristics of deviant adolescents, it is necessary to take into account age-related characteristics and a number of social life situations that directly determine and maintain a high level of deviations in society.